The Veblen-Gerschenkron Effect of FDI in Mezzogiorno and East Germany - Dieter M. Urban; Giovanni Peri (University of California, Department of Economics, 2002)
The presence of foreign multinational enterprises (MNEs) should benefit local economies. In particular if MNEs are particularly productive compared to domestic firms they may promote learning and catch-up of local firms. Such channel of spillovers from MNEs to local firms is known as the Veblen Geschenkron effect. Rather than the overall density of MNE in a region or sector, it is their productivity advantage on the local firm to determine the positive effect on domestic productivity growth.We test this hypothesis using firm level data for German and Italian company for the 90''s. and we find evidence of a significant and robust Veblen-Gerschenkrion effect. The initial total factor productivity advantage of MNEs on local firm acts as a stimulus for productivity growth of local firms in the same region.
Keywords: F23; O47; R11; 330; Veblen-Gerschenkron Effect; FDI; Spillovers; Productivity; Multinationales Unternehmen; Spillover-Effekt; Direktinvestition; Regionale Entwicklung; Produktivität; Vergleich; Schätzung; Italien <Süd>; Neue Bundesländer; Italien; Deutschland